Workplace Spirituality and Its Effects on Organizational Effectiveness - A Study of Healthcare Sales Professionals in Malaysia - Khong Loong, Jeffrey Yee (2010)
This study aimed to better understand the construct of Workplace Spirituality by attempting to break it down into appropriate mini-constructs. In doing so, this study was also able to look into the association of Workplace Spirituality with Workplace Performance. This is crucial in order for research and practice to be able to understand and apply the values and beliefs at work that enhance performance at work.